AMPHORAE IMPORTS IN SOUTHERN LUSITANIA (ALGARVE): Recent evidence from urban sites: the Roman town of Balsa - Viegas, Catarina (Rei Cretariae Romanae Fautorum Acta, 2024)
In recent years our research has focused on southern Portugal (specifically, on the Algarve region), which, in Roman times, was part of the province of Lusitania. The ongoing research project is centred in the study/analysis of different pottery categories from a number of different excavations that have taken place at the sites of Roman towns such as ancient Ossonoba (today Faro) and Balsa (Torre de Ares) or at the sites of smaller urban settlements, such as the ancient Baesuris (today Castro Marim). There was a clear option to focus on materials found at these sites and deposited in the Town Museum in Faro and in the National Museum of Archaeology in Lisbon.